Validation of an instrument of dental anxiety EQ-SDAI. - Villavicencio, Ebingen (2019)
Objective: The aim of this study was to validate an instrument of mass use to evaluate dental anxiety, by means of the dichotomization of a continuous variable of the Dental Anxiety Inventory short version instrument (SDAI) to a binary variable of the EQ- SDAI instrument. Material and Methods: One population aged >18 years were used in the analysis. The SDAI was cross-culturally adapted to Spanish, and was named EQ-SDAI, then sensibility and specificity was calculated also the ROC curve was used to assess the reliability of the new questionnaire. Point biserial correlation coeﬃcient was calculated. For the internal consistency analysis, the Kuder Richardson coeﬃcient (KR-20) was used. Results: High sensitivity (Sen = 0.93), and an acceptable specificity (Esp = 0.60) was obtained. Through the point biserial correlation coeﬃcient, a statistically significant result (R> 0.70) was obtained, in eight of the nine questions of the SDAI scale, which indicates that there is a good coeﬃcient of correlation. Conclusions: The internal consistency (KR-20) was 0.866.